Diet and eczema: a review of dietary supplements for the treatment of atopic dermatitis - Schlichte, Megan J. (Dermatol Pract Concept, 2016)
In the context of increasing popularity of “natural” alternatives to conventional medicine, several dietary supplements have gained the attention of researchers and consumers alike in the treatment of atopic dermatitis (AD). Readily available without a prescription and frequently perceived to have fewer side effects than traditional medications, these “natural” remedies may be featured in discussions with patients, and clinicians should therefore be familiar with their efficacy and safety. Based on trials to date, no dietary supplements can be recommended for routine use in the treatment of AD. However, some promising results have been noted from the use of probiotics and prebiotics taken in combination. Given significant differences in study design to date, however, further studies would be needed to clarify dose and strains of probiotics. Studies of vitamin D have been limited and have produced conflicting results, although further trials in selected subsets of patients may be indicated. Very limited data is available on fish oil supplements, while future studies on Chinese herbal medicine would require evaluation of comparable herbs and formulations. Finally, multiple trials of evening primrose oil and borage seed oil have shown improvement similar to placebo, and neither is currently recommended in eczema therapy.